Analytical Solution to 1D Compressible Navier-Stokes Equations. (27th May 2021) - Dou, Changsheng; Zhao, Zishu
Abstract : There exist complex behavior of the solution to the 1D compressible Navier-Stokes equations in half space. We find an interesting phenomenon on the solution to 1D compressible isentropic Navier-Stokes equations with constant viscosity coefficient on x, t ∈ 0, + ∞ × R +, that is, the solutions to the initial boundary value problem to 1D compressible Navier-Stokes equations in half space can be transformed to the solution to the Riccati differential equation under some suitable conditions.